Asia pacific financial markets in comparative perspective issues and implications for the 21st century - Thomas A. Fetherston; Jonathan A. Batten (Contemporary studies in economic and financial analysis, 2005)
The goal of the volume is to provide some background on the various financial market segments of the Asian Pacific region. An understanding of institutional detail (size and scope) of the relevant markets affords a view that lends or detracts from the credibility of intermarket comparisons. An exposure and understanding of institutional detail supplies information that may bear on the statistical results of the empirical analysis. The vital roles played bycapital markets of pricing capital, issuing new shares, providing a liquidity-creating secondary feature, serving as a vehicle for asset transfer, and providing a linkage to international capital markets are as important to emerging markets as to developed countries.